Modeling atmospheric and oceanic flows : insights from laboratory experiments and numerical simulations - Larcher, Thomas von.; Williams, Paul D. (Paul David), 1977- (Hoboken, N.J. : Wiley ; Washington, DC : American Geophysical Union, 2014)
Modeling Atmospheric and Oceanic Flows: Insights from LaboratoryExperiments and Numerical Simulations provides a broad overview ofrecent progress in using laboratory experiments and numericalsimulations to model atmospheric and oceanic fluid motions. Thisvolume not only surveys novel research topics in laboratoryexperimentation, but also highlights recent developments in thecorresponding computational simulations. As computing power growsexponentially and better numerical codes are developed, theinterplay between numerical simulations and laboratory experimentsis gaining paramount importance within the scientific community. The lessons learnt from the laboratory'model comparisons inthis volume will act as a source of inspiration for the nextgeneration of experiments and simulations. Volume highlightsinclude: -Topics pertaining to atmospheric science, climatephysics, physical oceanography, marine geology and geophysics -Overview of the most advanced experimental andcomputational research in geophysics -Recent developments in numerical simulations ofatmospheric and oceanic fluid motion -Unique comparative analysis of the experimentaland numerical approaches to modeling fluid flow Modeling Atmospheric and Oceanic Flows will be a valuableresource for graduate students, researchers, and professionals inthe fields of geophysics, atmospheric sciences, oceanography, climate science, hydrology, and experimental geosciences.
"This work is a co-publication between the American Geophysical Union and John Wiley & Sons, Inc."
Includes bibliographical references and index.
Online resource; title from PDF title page (EBSCO, viewed November 24, 2014).
Keywords: Atmospheric models; Ocean currents; Oceanography; SCIENCE -- Earth Sciences -- Geography; SCIENCE -- Earth Sciences -- Geology; Atmospheric models; Ocean currents; Oceanography; Electronic books